India's green revolution : economic gains and political costs - Frankel, Francine R. (Princeton legacy library., 1971)
The success of the agricultural policy adopted in 1965 has given India the hope of escaping from its circle of poverty. At the same time the increased rate of economic development seems to have exacerbated social tensions and accentuated disparities that may eventually undermine the foundations of rural political stability. Originally published in 1971. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts.